The CURB65 score predicted 180-day mortality of non-small cell lung carcinoma patients with immune checkpoint inhibitor-associated pneumonitis: A pilot retrospective analysis - Lan, Fen; Fan, Bo; Wang, Lihua; Xia, Lixia; Zhang, Ting; Li, Wen; Mao, Yanxiong (Frontiers in Oncology, 2022)
Introduction: The immune checkpoint inhibitor-associated pneumonitis (CIP) is a particularly worrisome and potentially lethal form of immune-related adverse events. An objective and evidence-based assessment tool for evaluating the severity of CIP is in urgent need. The CURB65 (consciousness, urea nitrogen, respiratory rate, blood pressure and age) is a potential candidate to meet the need. Methods: A retrospective study was conducted to explore preliminarily if CURB65 could predict the mortality in non-small cell lung carcinoma (NSCLC) patients with CIP. Results: A total number of 28 NSCLC patients with CIP were included in the current study, and classified into low CURB65 group (n=21) and high CURB65 group (n=7). Mortality after onset of CIP was consistently higher in the high CURB65 group than in the low CURB65 group (30-day: 57.1% vs 0; 90-day: 71.4% vs 4.76%; 180-day:71.4% vs 14.29%). Two patients (9.5%) in the low CURB65 group had severe CIP, and more than half of patients in the high CURB65 group had severe CIP (p=0.0008). The patients in high CURB65 group received more aggressive treatment. Both groups showed a predominant organizing pneumonia -like pattern on CT scan. The CURB65 was moderately correlated with American Society of Clinical Oncology (ASCO) grade of CIP, with a Pearson correlation coefficient R of 0.524. Conclusion: The CURB65 accurately stratified the risk of mortality in NSCLC patients with CIP. The CURB65 might complement the ASCO grade in the assessment and prediction of mortality in these population.